2012
DOI: 10.1210/jc.2011-1309
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up for Mortality and Cancer in a Randomized Placebo-Controlled Trial of Vitamin D3and/or Calcium (RECORD Trial)

Abstract: Daily vitamin D or calcium supplementation did not affect mortality, vascular disease, cancer mortality, or cancer incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(177 citation statements)
references
References 41 publications
5
166
0
6
Order By: Relevance
“…Few prospective intervention studies with sufficient statistical power have addressed this question. Both the Women's Health Initiative study, which followed .36,000 women, and the RECORD trial, which studied .5,000 patients, failed to show cardiovascular benefit (40,41), but metanalysis suggests the formulation of vitamin D may be important (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Few prospective intervention studies with sufficient statistical power have addressed this question. Both the Women's Health Initiative study, which followed .36,000 women, and the RECORD trial, which studied .5,000 patients, failed to show cardiovascular benefit (40,41), but metanalysis suggests the formulation of vitamin D may be important (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…This was however assessed in EPIC-Heidelberg, which showed that calcium supplements were used by less than 10% of subjects (42). Furthermore, results of a randomized controlled trial, investigating the risk of cancer death in over 5,000 subjects with previous fractures who were randomized to use calcium supplements, showed no association between calcium supplements use and cancer mortality (43). Nevertheless, the prediagnostic assessment and the lacking data on calcium supplements may have led, in combination with the self-reported design of the questionnaires, to attenuated risk estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Three randomized controlled trials of supplementation reported nonsignificantly lower overall cancer mortality with vitamin D supplementation (93)(94)(95) (Table 2), 1 of which also reported no effect on colon and respiratory cancer mortality (93). These trials were not powered for cancer mortality outcomes, however (96).…”
Section: Vitamin D Supplementationmentioning
confidence: 99%